Maxillary bone analysis in dentate and edentulous men through panoramic radiographs - Manja, Cek Dara; Siregar, Yudha Syah Agung (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI); Vol 7 No 3 (2023): Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2023)
Objectives: This study aims to analyze the height of maxillary bone in dentate and edentulous men through panoramic radiographs. Materials and Methods: This research is an analytic descriptive design with a cross-sectional approach. This study used 40 samples of panoramic radiography images, divided into groups of 20 edentulous men and groups of 20 dentate men as a control group. Maxillary bone height is measured by drawing a vertical line from the lowest point of the infraorbital ridge to the maxillary alveolar crest. Results: The result showed that the mean value of the dentate group samples was greater than that of the edentulous group. Conclusion: Dentate men have a higher maxillary bone height than edentulous men, as analyzed using panoramic radiography. There were significant differences in maxillary bone in edentulous and dentate men.